PENGARUH PROMOSI, PERSEPSI HARGA DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK PADA KARTU GSM IM3 KE SIMPATI (Studi Kasus Pada Mahasiswa Universitas Stikubank Semarang) - Eviliana Diska Bamanda, 12.05.51.0137; Budi Setiawan, Mulyo (Students Journal of Economic and Management, 2016)
The purpose of this research is to determine the effect of promotions, price perception, and the need to find variations, collectively or partially against the decision of brand switching on Im3 GSM card to Simpati. The data used in this research is the primary data. The population in this study is Stikubank Semarang University students who switch brands Im3 GSM Card to Simpati. Determination of the number of samples by using the formula Djarwanto and Subagyo. Based on this formula, then the sample size in this study as many as 100 students. The sampling technique using purposive sampling, namely choosing a sample in according with certain criteria. Data already collected then tabulated and tested by using validity and reliability. After fulfilling the criteria of valid and reliable, then the multiple linear regression analysis to obtain information about the effect of each independent variable on the dependent variable. These results indicate that brand switching decision positively and significantly influenced by promotions, price perception, and the need to find variations. The variable most dominant influence brand switching decision Im3 GSM Card to Simpati is Promotion. Keyword: promotions, price perception, the need to find variations, and brand switching decision.